Berberine is an insulin secretagogue targeting the KCNH6 potassium channel - Zhao, Miao-Miao; Lu, Jing; Li, Sen; Wang, Hao; Cao, Xi; Li, Qi; Shi, Ting-Ting; Matsunaga, Kohichi; Chen, Chen; Huang, Haixia; Izumi, Tetsuro; Yang, Jin-Kui (Nature communications, 2021)
Coptis chinensis is an ancient Chinese herb treating diabetes in China for thousands of years. However, its underlying mechanism remains poorly understood. Here, we report the effects of its main active component, berberine (BBR), on stimulating insulin secretion. In mice with hyperglycemia induced by a high-fat diet, BBR significantly increases insulin secretion and reduced blood glucose levels. However, in mice with hyperglycemia induced by global or pancreatic islet β-cell-specific Kcnh6 knockout, BBR does not exert beneficial effects. BBR directly binds KCNH6 potassium channels, significantly accelerates channel closure, and subsequently reduces KCNH6 currents. Consequently, blocking KCNH6 currents prolongs high glucose-dependent cell membrane depolarization and increases insulin secretion. Finally, to assess the effect of BBR on insulin secretion in humans, a randomized, double-blind, placebo-controlled, two-period crossover, single-dose, phase 1 clinical trial (NCT03972215) including 15 healthy men receiving a 160-min hyperglycemic clamp experiment is performed. The pre-specified primary outcomes are assessment of the differences of serum insulin and C-peptide levels between BBR and placebo treatment groups during the hyperglycemic clamp study. BBR significantly promotes insulin secretion under hyperglycemic state comparing with placebo treatment, while does not affect basal insulin secretion in humans. All subjects tolerate BBR well, and we observe no side effects in the 14-day follow up period. In this study, we identify BBR as a glucose-dependent insulin secretagogue for treating diabetes without causing hypoglycemia that targets KCNH6 channels. Berberine is a compound with glucose-lowering effects in mice and humans. Here, the authors show that in mice berberine has beneficial glycemic effects by promoting insulin secretion, which requires the potassium channel KCNH6 in beta cells, and that berberine can promote insulin secretion in healthy men in a phase 1 clinical trial.